Cram session in joint mobilization techniques : a handbook for students & clinicians - Berry, David C., 1971-; Berry, Leisha M., 1973- (Slack Incorporated, 2016)
"When all you need is a basic understanding of joint mobilization techniques, supplemented by succinct and demonstrative examples, look to Cram Session in Joint Mobilization Techniques: A Handbook for Students & Clinicians for quick, at-your-fingertips facts. Cram Session in Joint Mobilization Techniques by Dr. David C. Berry and Leisha M. Berry is a descriptive quick reference that provides the rehabilitation professional with a detailed yet easy-to-digest approach to joint mobilization techniques. Organized into quick-reference tables and concise descriptions of each technique, this resource offers an efficient way to learn the cognitive and psychomotor skills necessary to competently perform joint mobilization techniques. What is in your Cram Session: - Easy-reference tables of joint complex osteology and arthrology - Photographs depicting mobilization techniques for each joint - Case studies in mobilization - Quiz questions to test your knowledge Instructors in educational settings can visit www.efacultylounge.com for additional materials to be used for teaching in the classroom. Cram Session in Joint Mobilization Techniques: A Handbook for Students & Clinicians is an informative, well-organized handbook for all students and clinicians in athletic training, physical therapy, occupational therapy, osteopathic medicine, and other rehabilitation professions"--Provided by publisher